PENGARUH PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN BEDAK PADAT MAKE OVER PADA MAHASISWI - Mahrom DS, Yudha; Ramadhona Syafitri, Tamara; Herudiansyah, Gumar (Universitas Muhammadiyah Palembang, 2024)
Purpose– This research aims to determine the influence of Product, Price and Promotion simultaneously and partially on the Purchase Decision of Make Over Pressed Powder among Female Students of the Faculty of Economics and Business, Muhammadiyah University of Palembang.Design/methodology– The sample used was 100 respondents. The sampling technique uses non-probability sampling using purposive sampling. The type of research used is associative. The data used are primary and secondary data. The data collection technique is a questionnaire. The data analysis used is quantitative qualitative analysis. The analysis techniques used are validity test, multiple linear regression, F test, t test and coefficient of determination. The results of multiple linear regression analysis show that Product, Price and Promotion have a positive influence on purchasing decisions for Make Over Pressed Powder among female students at the Faculty of Economics and Business, Muhammadiyah University, Palembang.Findings - The results of simultaneous hypothesis testing (F) show that there is a positive and significant influence of Product, Price and Promotion simultaneously on purchasing decisions. The results of the t test hypothesis show that Product, Price and Promotion have a partially positive and significant effect on Purchasing Decisions. The coefficient of determination value shows that the Product, Price and Promotion variables influence the ups and downs of Purchasing Decisions, with a change of 54.1%.